Impact of School Environment on Teachers’ Performance at Primary Level - Dr. Qaisar Abbas; Mariam Javed; Madiha Waseem (Journal of Management Practices, Humanities and Social Sciences, 2022)
The main goal of this research study was to explore teachers’ perceptions about the “Impact of School Environment on Teachers’ Performance at primary level in Tehsil Chiniot.” The study has two objectives, a) to explore teachers’ perceptions of the school’s environment and b) to explore its impact on teachers’ performance. The population of this study was all the teachers working in government primary schools in tehsil Chiniot. A sample of 96 primary teachers was selected through the convenience sampling technique. Data were collected from the teachers through the researcher’s designed, validated and reliable instrument (questionnaire) based on a five-point Likert scale and having twenty positive statements. Data were analyzed through SPSS (version 24) statistical software, and mean, frequency, percentages, and correlation tests were computed. The results of this study revealed that most teachers agreed that the school’s environment influences their performance and students’ performance. This study exposed a statistically significant positive relationship between the school environment and teachers’ performance. The study recommended that the government, policymakers, and heads should provide sufficient facilities to improve the schools’ environment at the primary level in Tehsil Chiniot.